2010
DOI: 10.5012/bkcs.2010.31.04.825
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Roots of Glycyrrhiza Species by1H Nuclear Magnetic Resonance Spectroscopy and Multivariate Statistical Analysis

Abstract: To classify Glycyrrhiza species, samples of different species were analyzed by 1 H NMR-based metabolomics technique. Partial least squares discriminant analysis (PLS-DA) was used as the multivariate statistical analysis of the 1 H NMR data sets. There was a clear separation between various Glycyrrhiza species in the PLS-DA derived score plots. The PLS-DA model was validated, and the key metabolites contributing to the separation in the score plots of various Glycyrrhiza species were lactic acid, alanine, argin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…2224 However, as demonstrated above, macroscopic identification is insufficient to detect Glycyrrhiza hybrids. All licorice roots/rhizomes are similar macroscopically and microscopically.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2224 However, as demonstrated above, macroscopic identification is insufficient to detect Glycyrrhiza hybrids. All licorice roots/rhizomes are similar macroscopically and microscopically.…”
Section: Resultsmentioning
confidence: 99%
“…16,1924 Metabolomic analyses of licorice roots were initiated by Yang and co-workers, 22 who performed 1 H NMR multivariate analysis on botanically and macroscopically identified Glycyrrhiza species focusing on primary metabolites. 22 Subsequently, Farag and co-workers 23 combined LC-MS and 1 H NMR metabolite profiling of botanically and macroscopically identified Glycyrrhiza species, using three sample acquisitions per species. Recently, we have demonstrated that both major Fs and their C isomers coexist in extracts from licorice roots and can be determined as pairs of isomers.…”
mentioning
confidence: 99%
“…However, selection of highly productive lines and optimization of chemical and physical culture milieu of the cells for copious production is a prerequisite for the commercial application of these systems. It has been demonstrated that the biosynthetic activity of cultured cells can be enhanced by regulating various factors like environment (Ayabe et al 1990), selecting hyper-producing lines (Jiao et al 2014;Mardamshin et al 1994) precursor feeding (Yang et al 2007a(Yang et al , 2010 and transformation method . The expanding commercial importance of the plant based anti-cancer compound has kindled the researchers to look for their production in tissue culture system.…”
Section: Introductionmentioning
confidence: 99%
“…The metabolites such as 2-Oxoglutarate and Taurine alone were present in As 2 O 3 tolerant plants, but absent in in vitro control plants of A. paniculata. Similarly, the different samples of Glycyrrhiza species were examined by 1D 1 H NMR-based metabolomics analysis (Yang et al, 2010). Anand et al (2011) also reported the various bioactive chemical compounds by NMR spectral analysis in Zehneria scabra.…”
Section: Metabolomic Analysis By 1d 1 H-nmrmentioning
confidence: 99%